ARTIFICIAL INTELLIGENCE AS A GOVERNANCE INFRASTRUCTURE: RETHINKING HEALTH SYSTEMS IN AFRICA - David Mhlanga (Veredas do Direito, 2026)
This paper reconceptualises Artificial Intelligence (AI) as a governance infrastructure within African health systems. Many health systems across Africa face structural constraints, including workforce shortages, fragmented data systems, and limited infrastructure, which undermine service delivery and equity. The paper argues that AI enables a transition from reactive, fragmented systems to predictive, integrated, and data-driven governance models. It examines key applications in diagnostics, disease surveillance, supply chain management, and telemedicine, highlighting how AI improves decision-making, resource allocation, and access to care. At the same time, the study identifies critical challenges, including data privacy risks, algorithmic bias, and technological dependency. The findings suggest that the transformative potential of AI depends on strong governance frameworks, institutional capacity, and locally grounded policies. By positioning AI as a governance infrastructure, the paper contributes to understanding how digital innovation can strengthen resilience, efficiency, and equity in African health systems.